An International Comparison of Income and Hours of Work - Winston, Gordon C. (The Review of Economics and Statistics, 1966)
T HIS paper reports on a study of the relation between peoples' incomes and the way they allocate their time to income and leisure. Time can be spent either on the earning of income (work) or on a host of alternative noneconomic activities (leisure). It is a question of real significance whether, as incomes rise, people systematically change their distribution of time between these activities. However, it is a question to which economics provides no agreed upon answer. No a priori or theoretical answer is possible because we know that, as sellers of their own time, people are pulled in opposite directions by conflicting income and substitution effects. On the other hand, no empirical evidence has thus far been widely accepted despite surprisingly consistent empirical results. But since economic growth and rising incomes are part of a pervasive economic climate, this aspect of peoples' behavior the way they respond to increased economic well-being is of very real importance, in part because it will feed back as an influence on the rate and pattern of growth itself, both in advanced and in underdeveloDed countries.' This subject, of course, is discussed in the theory of public finance as the incentive effect of tax and expenditure, in macro and labor theory as the shape of the long-run aggregate labor supply curve, and in the literature of economic development as the response to changing sectoral terms of trade. This study is empirical. It uses aggregate international cross-sectional data to reveal the typical relation between incomes and hours of work-i.e., between incomes and the allocation of effort (as synonymous with time) to the acquisition of income. Previous empirical studies either have shown that relationship to be negative -work effort decreases with increasing incomes or at the least, have failed to show a positive correlation. The data used in those earlier studies were intercity and interindustry cross-sections [2, 7, 8], industry data over time [71, and cross-sections of occupational sub-groups within a society [2]. The major purpose of this study is to test the conclusions of those earlier investigations to see if these very different international aggregate data confirm that the relation is negative. A secondary objective is to use these data to evaluate possible influences, additional to income, on a society's allocation of effort.